DIDACTIC FEATURES OF THE METHODS USED IN TECHNICAL CREATIVITY - Dilshod Bakhtiyorovich Luxmanov (Web of Journals Publishing, 2024)
In this article of three articles, some considerations are mentioned about the didactic features of the methods used in technical creativity.
Keywords: Technical creativity, didactics, interactive method, brainstorming, methodology.